PENGARUH ELEVASI KAKI TERHADAP TEKANAN DARAH PADA PASIEN SECTIO CAESARIA DENGAN SPINAL ANESTESI DI INSTALASI KAMAR BEDAH RUMAH SAKIT TK.II ROBERT WOLTER MONGISIDI MANADO - Arfisco Oroh; Danang Tri Yudono; Adiratna Sekar Siwi (Sekolah Tinggi Pariwisata Mataram, 2022)
Sectio Caesaria (SC) is one of the most common procedures performed today to assist the birth of the fetus by making an incision in the uterine wall and abdomen. As a surgical procedure, the implementation of SC requires anesthesia where the anesthetic technique that is often used is spinal anesthesia. Unexpected complications from spinal anesthesia are possible, changes in blood pressure are one of the complications that often occur in the administration of spinal anesthesia. This study aims to determine the effect of leg elevation on blood pressure after spinal anesthesia in SC patients. This research method employs a nonequivalent control group design model and a quasi-experimental desig. The sampling technique used the purposive sampling technique as many as 58 respondents with 29 respondents in each group, the control group and the intervention group. Data were taken by measuring blood pressure before and after spinal anesthesia. Based on the results of the independent t-test, it can be seen that post spinal anesthesia systolic BP at 10 minutes Sig. (2-tailed) 0.000 <0.05 and post spinal anesthesia diastolic BP at 10 minutes Sig value. (2-tailed) 0.000 <0.05 which means Ha is accepted. Thus, it can be said that there is an effect of leg elevation on blood pressure after spinal anesthesia in sectio caesaria patients. Leg elevation influences blood pressure after spinal anesthesia in cesarean section patients.